(untitled) (Journal of Health, Population and Nutrition, 2012)
The balance between free radical production and antioxidant defenses in the body has important systemic and oral health implications. There is convincing evidence that breastmilk containing antioxidants is important in the prevention of diseases in infancy. This study compared the total antioxidant concentration of human breastmilk expressed at different stages of lactation, stored at various temperatures and durations. Expressed breastmilk (EBM) samples of the third, seventh and 30th day were collected from women who had term and preterm deliveries (n=20). Another cohort of women (n=20) was also assessed; these women were more than five months postpartum and lactating. The total antioxidant capacity (TAC) of EBM was assessed at zero hours at room temperature, at 48 hours, one week post-refrigeration (4 °C), and freezing (-8 °C) respectively using the phosphomolybdenum method. The highest antioxidant levels were found in colostrum. The TAC of EBM reduced with time and at post-refrigeration and after freezing (p<0.0005). No significant difference in the mean TAC was observed between the EBM samples obtained from women with either term or preterm deliveries. The progressive loss of antioxidant content of EBM emphasizes the need of awareness and curtailment of the practice of storing and later use of EBM. DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9897 JHPN 2011; 29(6): 605-611